Pollen abundances of sediment core FLB from Lake Flocktjärn (Sweden) from 2014 - Stefan Engels (PANGAEA, 2022)
This dataset provides pollen counts for the Holocene sediment sequence retrieved from Lake Flocktjärn (Sweden) in 2014. The counts are presented against both depth (m) and age (ka BP). A total of 44 samples were counted. A total of 44 samples were counted. The pollen record provides information about both regional vegetation change as well as changes in the within-lake flora. It was produced to inform on the exact age and duration of major palynological transitions during the Holocene. Cores were retrieved from the lake using a 1-m long handheld piston corer deployed from a floating coring platform during field work in May 2014. Volumetric samples were obtained from splits of the core and processed in the laboratory (University of Amsterdam, the Netherlands) using standard protocols.